The Influence of the Fashion Style used by Influencers on the Appearance Style of Generation Z - Rusdi Hidayat; Acep Samsudin; Arya Mahardika P; Muhammad Qowiyyudin; Decinta Putri A; Faradilla Aghnia A; Nafa Shoimah (CV. Rayyan Dwi Bharata, 2022)
Influencers who have many fans, so that it becomes the spotlight of generation Z to be an inspiration for the fashion style that is being used. This study aims to determine the influence of the fashion style used by influencers on the appearance style of generation Z. Generation Z is a generation that has very unique and different characters from previous generations. Meanwhile, an influencer is someone who has a lot of followers so that it gives potential for their fans to follow, starting from fashion style and lifestyle, and most of those who become fans of an influencer are generation Z. This research uses descriptive qualitative which shows the results that in expressing themselves, generation Z one of them is the fashion she wears. The development of fashion is very fast at the age of generation Z. They are more concerned with their physical appearance than everything